1990
DOI: 10.2307/1510657
|View full text |Cite
|
Sign up to set email alerts
|

Learning Disabilities Definitions and Criteria Used by State Education Departments

Abstract: This article reports the results of a survey of the 51 State Departments of Education (including Washington, DC) regarding their learning disabilities definitions, identification criteria, and operationalization procedures. A conceptual framework consisting of eight components was used in analyzing the definitions and identification criteria. While revealing variations, results showed the continued impact of the 1977 federal definition and criteria. For example, several state definitions now include the discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 18 publications
0
83
0
3
Order By: Relevance
“…Most current educational systems in the United States determine eligibility for special education assistance based on IQdiscrepancy definitions (Mercer et al, 1996). Students who demonstrate a discrepancy between reading achievement and intelligence are provided with special education assistance, while students who demonstrate poor reading achievement commensurate with their intelligence are often denied special assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Most current educational systems in the United States determine eligibility for special education assistance based on IQdiscrepancy definitions (Mercer et al, 1996). Students who demonstrate a discrepancy between reading achievement and intelligence are provided with special education assistance, while students who demonstrate poor reading achievement commensurate with their intelligence are often denied special assistance.…”
Section: Discussionmentioning
confidence: 99%
“…IDEA loosely regulates SLD identification and thus largely leaves operationalization of identification practices up to individual states resulting in considerable variability in how students are identified with SLD across states (Maki et al, 2015;Reschly & Hosp, 2004). Reviews of state SLD identification practices, when taken together, suggested that identification practices shifted over time; but, even before the reauthorization of IDEA in 2004, consistent SLD identification practices were not evident (Mercer, Hughes, & Mercer, 1985;Mercer, Jordan, Allsopp, & Mercer, 1996;Mercer, King-Sears, & Mercer, 1990;Reschly & Hosp, 2004).…”
Section: Sld Identification Practicesmentioning
confidence: 99%
“…Exactly how to compute difference scores is not specified in federal guidelines, but some states have adopted specific methodologies. The most popular method (Mercer, King-Sears, & Mercer, 1990) is probably the simple difference score method, in which the ability and achievement scores are standardized (to have equivalent means and standard deviations) and the difference taken; however, there are methodological limitations involved in computing the difference in this way (Evans, 1992a;Reynolds, 1984). The main problem with the simple difference score method is that it fails to take into account "regression toward the mean," which is an egregious omission in this case because the typical correlation between ability and achievement, as measured by the most popular tests, is about .60 (Wilson & Cone, 1984).…”
mentioning
confidence: 99%
“…With this rationale, the relevant difference to compute is that between an examinee's observed achievement and expected achievement scores, not that between observed ability and observed achievement scores. Nevertheless, the regression method is not used as often as the simple difference method (Mercer et al, 1990), and this is at least in part due to the computational demands of the former method (Evans, 1992b). In fact, the regression method is so complex to implement that special computer programs have been designed to perform the analyses (Evans, 1993).…”
mentioning
confidence: 99%